Morphological features of the respiratory part in guinea pigs lung in dynamics of experimental allergic inflammatory process - Popko, S. S.; Попко, Світлана Сергіївна (My University, 2022)
The main function of the components of the respiratory tract is gas exchange while maintaining homeostasis in lung, given the pathogenic and non-pathogenic elements of the environment contained in the inhaled air. Morphological changes of the components of the respiratory part in lung of human and animals of adaptive nature under the influence of various factors on the body today remain insufficiently studied. The aim of the study was to investigate the morphological changes of the components of the respiratory part of guinea pigs lung in the dynamics of experimental ovalbumin-induced allergic inflammation. We used histological and electron microscopic methods to study the lungs of 48 male guinea pigs in experimental ovalbumin-induced allergic inflammation, simulated by subcutaneous sensitization and subsequent intranasal inhalation with ovalbumin. Morphological changes of the components of the respiratory tract of the lungs were determined in the early and late phases of allergic inflammatory process at the optical and submicroscopic levels. The early phase (23rd and 30th days of the experiment) was characterized by a predominance of alterative and destructive changes, consisted in the desquamation of the alveolar epithelium with a violation of the blood-gas barrier and hemomicrocirculatory bed. Type II alveolar cells had lesions of varying severity in the form of the absence of lamellar bodies or disturbances in the formation of their contents, vacuolization of the cytoplasm, mitochondrial damage. In the late phase of the development of the allergic inflammatory process (36th and 44th days of the experiment) in the respiratory part of lung were dominated adaptive and restorative changes. In addition, we observed dilation of the lung alveoli and thinning of the interalveolar septa, which is a consequence of the cascade of reactions of the local neuroendocrine and immune systems of lung as a result of allergen action. Thus, experimental ovalbumin-induced allergic inflammatory process of the respiratory tract is accompanied by structural and functional changes in the components of the respiratory part in lung of guinea pigs in stages depending on the duration of the experiment. Основна функція компонентів респіраторного відділу легень полягає в газообміні та забезпеченню гомеостазу в легенях, враховуючи патогенні та непатогенні елементи навколишнього середовища, які містяться у повітрі, що вдихається. Морфологічні зміни компонентів респіраторного відділу легень людини і тварин адаптаційного характеру при дії на організм різноманітних чинників на сьогоднішній день залишаються недостатньо дослідженими. Мета роботи - дослідити морфологічні зміни компонентів респіраторного відділу легень морських свинок в динаміці експериментального овальбумініндукованого алергічного запалення. За допомогою гістологічного та електронно-мікроскопічного методів вивчили легені 48 самців морської свинки в умовах експериментального овальбумін-індукованого алергічного запалення, яке моделювали шляхом підшкірної сенсибілізації та наступної інтраназальної інгаляції овальбуміном. На світлооптичному та субмікроскопічному рівнях визначали морфологічні зміни компонентів респіраторного відділу легень в ранньому та пізньому періодах алергічного запального процесу. Ранні стадії (23 та 30 доба експерименту) характеризувались переважанням альтеративних і деструктивних змін, котрі полягали в десквамації коміркового епітелію з порушенням аерогематичного бар'єру й гемомікроциркуляції. Альвеолоцити ІІ типу мали ушкодження різного ступеня тяжкості у вигляді відсутності пластинчастих тілець або порушення у формуванні їх вмісту, вакуолізації цитоплазми, пошкодження мітохондрій. У пізні стадії розвитку алергічного запального процесу (36 і 44 доба експерименту) в респіраторному відділі легень переважали адаптаційно-відновні зміни. Крім того, ми спостерігали розширення легеневих комірок та витончення міжкоміркових перегородок, що є наслідком каскаду реакцій локальної нейроендокринної та імунної систем легень в результаті дії антигену. Таким чином, експериментальний овальбумін-індукований алергічний запальний процес супроводжувався структурнофункціональними змінами компонентів респіраторного відділу легень морських свинок, які відрізнялися у ранній та пізній фазах запального процесу залежно від тривалості експерименту.
Морфологічні особливості респіраторного відділу легень морських свинок в динаміці експериментального алергічного запального процесу
Keywords: alveolar epithelium; surfactant; allergic inflammation; ovalbumin; guinea pig; комірковий епітелій; сурфактант; алергічне запалення; овальбумін; морська свинка